1990
DOI: 10.1083/jcb.110.6.1861
|View full text |Cite
|
Sign up to set email alerts
|

Primary sequence and heterologous expression of nuclear pore glycoprotein p62.

Abstract: Abstract. The major nuclear pore protein p62 is modified by O-linked N-acetylglucosamine and functions in nuclear transport. We have cloned, sequenced, and expressed the full-length rat p62 cDNA. The rat p62 mRNA is 2,941 nucleotides long and encodes a protein of 525 amino acids containing 30% serine and threonine residues. The amino acid sequence near the amino-terminus contains unique tetrapeptide repeats while the carboxy-terminus consists of a series of predicted alpha-helical regions with hydrophobic hept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(69 citation statements)
references
References 27 publications
2
67
0
Order By: Relevance
“…RanGDP did not bind significantly to RanBP2 ( Figure 5A) or to RanBP1 (our unpublished results) under these conditions. We also used the microtiter plate-binding assay to compare the binding affinity of p97 for RanBP2 and for p62, a nucleoporin that does not bind Ran but that also contains FG repeats (Starr et al, 1990). We found that p97 bound both to RanBP2 ( Figure 5B) and to p62 ( Figure 5C) with an apparent K d of 14 nM.…”
Section: Characterization Of the Binding Of P97 And Ran To Ranbp2mentioning
confidence: 99%
“…RanGDP did not bind significantly to RanBP2 ( Figure 5A) or to RanBP1 (our unpublished results) under these conditions. We also used the microtiter plate-binding assay to compare the binding affinity of p97 for RanBP2 and for p62, a nucleoporin that does not bind Ran but that also contains FG repeats (Starr et al, 1990). We found that p97 bound both to RanBP2 ( Figure 5B) and to p62 ( Figure 5C) with an apparent K d of 14 nM.…”
Section: Characterization Of the Binding Of P97 And Ran To Ranbp2mentioning
confidence: 99%
“…The list includes p62 [3,29], Nup153 [31], Nup155 [23], CAN/Nup214 [9], Nup98 [21,22], and RanBP/Nup358 [35,36]. These nucleoporins share the same XFXFG or GLFG repetitive sequence motifs, which are considered to be a nucleoporin signature.…”
mentioning
confidence: 99%
“…Of the estimated 60-100 different polypeptides that comprise the nuclear pore, only a handful have been identified. These include a component of the basket (nup153), proteins of the central region of the pore (p62/nup60, nup58, and nup54), components of the cytoplasmic filaments (nupl80, nup200/CAN, and TPR), and integral membrane pore proteins (gp210 and POM121), among others (Davis and Blobel, 1986;Starr et al, 1990;Cordes et al, 1991;Finlay et al, 1991;Hallberg et al, 1993;Radu et al, 1993;Sukegawa and Blobel, 1993;Wilken et al, 1993;Byrd et al, 1994; see Rout and Wente, 1994, for a review). A family of pore glycoproteins that contain N-acetylglucosamine residues and consequently bind the lectin WGA are among these pore proteins (for reviews, see Hart et al, 1989;Forbes, 1992;Rout and Wente, 1994).…”
mentioning
confidence: 99%